The Relationship of Health Belief Model Components with Hepatitis B Vaccination Compliance among Nurses at RSUD H.M. Ryacudu Kotabumi [Accepted] - Bambang Setiaji; Sugeng Eko Irianto; Arifaa Thalitha Zuleikha; Dian Utama Pratiwi Putri (Health Dynamics, 2026)
Background: Hepatitis B remains a significant global health problem due to its potential to cause chronic liver disease, cirrhosis, and hepatocellular carcinoma. Healthcare workers, particularly nurses, are at high risk of occupational exposure to the Hepatitis B virus through contact with blood and body fluids. Although vaccination is a highly effective preventive measure, compliance with complete Hepatitis B vaccination among nurses is still suboptimal, which may increase the risk of infection and transmission in healthcare settings. This study aimed to determine the relationship between the components of the Health Belief Model (HBM) and Hepatitis B vaccination compliance among nurses at RSUD H.M. Ryacudu, Kotabumi, North Lampung, in 2026. Methods:  This study used an analytic quantitative design with a cross-sectional approach. A total of 105 nurses were selected using proportionate stratified random sampling. Data were collected using structured questionnaires based on HBM components, including perceived susceptibility, perceived severity, perceived benefits, perceived barriers, cues to action, and self-efficacy. Data analysis was performed using univariate analysis, bivariate analysis with the Chi-square test, and multivariate analysis using logistic regression. Results: The results showed that 71 respondents (67.6%) were compliant with Hepatitis B vaccination. Bivariate analysis indicated significant relationships between perceived susceptibility (p=0.003), perceived severity (p=0.000), perceived benefits (p=0.000), perceived barriers (p=0.000), cues to action (p=0.000), and self-efficacy (p=0.000) with vaccination compliance. Multivariate analysis revealed that perceived benefits were the most dominant factor associated with vaccination compliance (p=0.003; OR=13.63).  Conclusions: The components of the Health Belief Model are significantly associated with Hepatitis B vaccination compliance among nurses. Enhancing education on vaccination benefits and strengthening institutional support are essential strategies to improve compliance among healthcare workers.